2023
DOI: 10.3390/su15054251
|View full text |Cite
|
Sign up to set email alerts
|

A Worrying Future for River Flows in the Brazilian Cerrado Provoked by Land Use and Climate Changes

Abstract: In this study, we assessed the impacts of land use and climate changes on the river flows of 81 watersheds within the Cerrado biome, Brazil, based on a comprehensive analysis of field and secondary data acquired between 1985 and 2018. Complementarily, we projected a future deforestation and climate scenario up to 2050 and predicted their impacts on surface water in the study area. We observed that direct impacts by large-scale deforestation oriented to the production of irrigated agricultural commodities have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 61 publications
0
5
0
2
Order By: Relevance
“…Dessa forma, informações acerca da dinâmica espaço-temporal dos pivôs são fundamentais do ponto de vista econômico, social e ambiental (Albuquerque et al, 2020). Essas informações são indispensáveis para a funcionalidade dos instrumentos de controle e gestão da água e que, por sua vez, são fundamentais para uma agricultura mais sustentável, principalmente no Cerrado, considerando-se os estudos que mostram que, até 2050, o bioma pode perder um terço de suas águas (Salmona et al, 2023).…”
Section: Anounclassified
“…Dessa forma, informações acerca da dinâmica espaço-temporal dos pivôs são fundamentais do ponto de vista econômico, social e ambiental (Albuquerque et al, 2020). Essas informações são indispensáveis para a funcionalidade dos instrumentos de controle e gestão da água e que, por sua vez, são fundamentais para uma agricultura mais sustentável, principalmente no Cerrado, considerando-se os estudos que mostram que, até 2050, o bioma pode perder um terço de suas águas (Salmona et al, 2023).…”
Section: Anounclassified
“…The process is repeated 10 times to obtain 10 goodness-of-fit values. In addition to the sample data, all of the above steps are also applied to the entire observation dataset (Salmona et al, 2023).…”
Section: Land Use Change Modellingmentioning
confidence: 99%
“…For instance, Machado et al (2019) identified a 9% gap in data over a 13-year time series from 564 INMET weather stations distributed across the entire Brazilian territory. Similarly, Salmona et al (2023) noted a 7% gap in precipitation data for various pluviometric stations of the National Water Agency (ANA) throughout the Cerrado biome. These instances underscore the importance of addressing data gaps when conducting ET calculations, especially when relying on physical weather station data.…”
Section: Introductionmentioning
confidence: 97%